2023
DOI: 10.36227/techrxiv.21432012.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human-as-a-Robot Performance in Augmented Reality Teleultrasound

Abstract: <p> <strong>Purpose:</strong> In “human teleoperation” [1], augmented reality (AR) and haptics are used to tightly couple an expert leader to a human follower. To determine the feasibility of human teleoperation, we quantify the abil- ity of humans to track a position and/or force trajectory via AR cues. The human response time, precision, frequency response, and step response were characterized, and several rendering methods were compared. </p> <p><strong>Methods:</stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The -3 dB cut-off frequency was set to 400 Hz since interactions with stiff environments can lead to high force bandwidths. The phase delay is < 1 • until approximately 10 Hz, which is the maximum typical for forces applied by the human hand [46].…”
Section: Sensor Module Pcbsmentioning
confidence: 98%
See 1 more Smart Citation
“…The -3 dB cut-off frequency was set to 400 Hz since interactions with stiff environments can lead to high force bandwidths. The phase delay is < 1 • until approximately 10 Hz, which is the maximum typical for forces applied by the human hand [46].…”
Section: Sensor Module Pcbsmentioning
confidence: 98%
“…The master board takes in all the readings from the SMs, combines and processes them on an ESP32-WROOM-32e microcontroller, and sends the resultant force/torque measurements to the host PC or other device. An inertial measurement unit (IMU) is also included on the board for pose estimation [44], and communicates over I2C with the ESP32. The microcontroller has two cores, allowing parallel processing, and two SPI drivers.…”
Section: Master Pcbmentioning
confidence: 99%
“…From tests it was found that typical hand motion during tracking was slow enough that the sampling rate of the vision system was sufficient. Indeed, the human hand bandwidth for applying forces is approximately 7 Hz [59], and the vision system runs at 22 Hz (see below). The vision system is thus beyond the Nyquist rate for hand motions.…”
Section: Kalman Filter With Imumentioning
confidence: 99%